Cloudberry (Rubus chamaemorus L.) Supplementation Attenuates the Development of Metabolic Inflammation in a High-Fat Diet Mouse Model of Obesity - Pemmari, Toini; Hämäläinen, Mari; Ryyti, Riitta; Peltola, Rainer; Moilanen, Eeva
2022